2021
DOI: 10.1021/acssuschemeng.1c06252
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Diffusivities of HFC-32 and HFC-125 in Ionic Liquids for the Separation of R-410A

Abstract: Current legislation calling for the phase out of hydrofluorocarbon (HFC) refrigerants is driving a global market shift that has prompted industry and research institutions to investigate new refrigerant mixtures and sustainable separation techniques for recycling refrigerants. The recent American Innovation and Manufacturing (AIM) Act of 2020 requires an 85% phase down of HFC production over the next 15 years. To achieve this goal, azeotropic refrigerant mixtures, such as R-410A composed of 50 wt % HFC-32 (dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 41 publications
4
56
0
Order By: Relevance
“…As expected, we find that the predictions utilizing M T , which has no κ temperature dependence and was calibrated only with experimental ternary data, has a 1% in-sample MAPE. In contrast, we find that the predictions of M B and M B,K (both models only calibrated with experimental binary solubility data) have an out-of-sample MAPE of 10.1% and 10.2%, compared to the ternary experimental compositions in Baca et al 56 The error is consistent with the difference observed between the data sets in Figure 3. We emphasize these measurements we obtained with different experimental methods and equipment (as described in the references), so a modest difference is to be expected.…”
Section: Peng-robinson Eos Accurately Describes Hfc/il Binary Solubil...supporting
confidence: 84%
See 4 more Smart Citations
“…As expected, we find that the predictions utilizing M T , which has no κ temperature dependence and was calibrated only with experimental ternary data, has a 1% in-sample MAPE. In contrast, we find that the predictions of M B and M B,K (both models only calibrated with experimental binary solubility data) have an out-of-sample MAPE of 10.1% and 10.2%, compared to the ternary experimental compositions in Baca et al 56 The error is consistent with the difference observed between the data sets in Figure 3. We emphasize these measurements we obtained with different experimental methods and equipment (as described in the references), so a modest difference is to be expected.…”
Section: Peng-robinson Eos Accurately Describes Hfc/il Binary Solubil...supporting
confidence: 84%
“…49,50 Regression of thermodynamic models Because equations of state (EoS) are continuous and differentiable functions, they are wellsuited for computer-aided process design and optimization. [51][52][53] EoS models, including van der Waals, 54,55 Peng-Robinson, 56 Redlich-Kong, 18,19 and soft-SAFT EoS, 57 have been shown to reliably predict thermodynamic properties of HFC and IL mixtures. Yet, many of these models include parameters which must be calibrated from data before they are used in process design.…”
Section: Ionic Liquids As Entrainersmentioning
confidence: 99%
See 3 more Smart Citations